Associations between Serum Ferritin Levels, Age-stratified Hematological Parameters, and Hemoglobin A2 Levels in Iraqi Beta Thalassemia Carriers - Zainab W. Al-Maaroof; Liqaa Mohammed Al Sharifi (Journal of Applied Hematology)
BACKGROUND: Beta-thalassemia trait (BTT), a prevalent hemoglobinopathy in Iraq, requires precise diagnostic strategies to address phenotypic variability influenced by iron status. Serum ferritin and hemoglobin A2 (HbA2) levels are critical markers; however, their interplay with age-stratified hematological parameters remains underexplored in high-prevalence regions. OBJECTIVES: This cross-sectional study aimed to evaluate serum ferritin levels in Iraqi BTT carriers and correlate them with HbA2, erythrocyte indices, and age-dependent hematological variations to refine the diagnostic and management protocols. METHODS: A cohort of 115 BTT carriers from Hilla City, Iraq, underwent hematological profiling using high-performance liquid chromatography, complete blood count, and serum ferritin quantification. Participants were stratified by age (1–5, 6–18, and >18 years) and ferritin status (low, normal, and high). RESULTS: Age-stratified analysis revealed significant increases in hematocrit: 30.54% ± 1.92%–34.6% ± 5.29, P < 0.01 and ferritin (78.8 ± 58.9 ng/mL to 108.5 ± 75.8 ng/mL, P < 0.01) with advancing age, alongside declining hemoglobin F: 2.82% ±3.09%–1.48% ±1.33, P = 0.015. Low ferritin correlated with exacerbated microcytosis (mean corpuscular volume: 53.08 ± 4.35 fL vs. 62.42 ± 5.34 fL, P < 0.001) and suppressed HbA2 (4.1 ± 0.48% vs. 4.8 ± 0.6%, P = 0.01). CONCLUSION: Iron deficiency, observed in a subset of carriers, exacerbates microcytic-hypochromic indices and marginally lowers HbA2 levels, whereas age-dependent hematological trends necessitate stratified diagnostic thresholds. Integrating ferritin assessments enhances the diagnostic accuracy of the BTT, particularly in resource-limited settings. HbA2 retains diagnostic reliability, but concurrent iron profiling is imperative to mitigate phenotypic misinterpretation.